Polyterritorial polygyny in the pied flycatcher - Rätti, Osmo (1993)
After having attracted their first female most pied flycatcher (Ficedula hypoleuca) males establish a second, spatially separate, territory and attempt to attract a second female there. Some males succeed in attracting the second female. Polygynous mating is costly for a secondary female since males feed primarily the young of the primary female and many of secondary females have to raise their nestlings alone. Why are males polyterritorial and why do some females accept a secondary status? First, males may space out territories in order to hide their mating status and therefore females are deceived into polygyny against their best interests. Alternatively, males may be polyterritorial to reduce aggression between their two mates. Some females may do their best by accepting polygyny because the cost of searching for an unmated male may exceed the cost of reduced male assistance. Females did not effectively avoid polygyny even though there were optional unmated males close by and it would have been adaptive to mate with an unmated male. There were some cues females might have been able to use to estimate male's mating status. Already mated polyterritorial males spent less time and sang less on their second territories than did unmated males on their single territories. The overlap in behaviour of males of different mating status might prevent females to accurately determine male's mating status. The power of female aggression seemed to be too weak to prevent male's secondary mating even when the distance between territories was short. The most plausible explanation for polyterritorial polygyny in the pied flycatcher is that males derive benefits from imperfect female choice by being polyterritorial.